Application of Ergonomic Architecture in Child-Friendly Furniture Design - Khairuni, Zhilli Izzadati; Yacub, Mirzal; Manik, Kharisma Roh Turang Gajah; Rani, Cut Meuthia; Trimailuzi, Trimailuzi (Universitas Muhammadiyah Surakarta, 2025)
The state's commitment to ensure child protection in the Constitution No. 16 of 2016 concerning child protection, states that every child has the right to survival, growth, and development as well as the blessing of protection from violence and discrimination. Research conducted by Susenas and Riskesdas (2018), based on data from the National Socio-Economic Survey Integration, the analysis of the Early childhood development Index (ECDI) is known whether an early childhood has developed well according to its stages and age. These developments not only aim to ensure good literacy, numeracy, physical, social-emotional, and learning skills, but also pay attention to the fulfillment of health, nutrition, and care and nurturing aspects. However, it is different from the conditions in North Sumatra, based on data from BPS Medan City, where children aged 36-59 months have not developed physical abilities according to their stages. Therefore, this study was conducted to examine the application of ergonomic architecture in child-friendly furniture design as a form of needs to support children's learning and play activities. The method used is in the form of qualitative descriptive with a design thingking method approach and the application of ergonomic architecture in a child-friendly furniture design, data collected at a PAUD in Medan City to children with an age range of 0-6 years through observation and interviews. The results of this study show that child development through sensory can be optimized with furniture design that suits children's needs, the concept of child-friendly furniture design as a reference and an alternative approach to early childhood development with the application of ergonomic architecture in optimizing growth and development as well as a guide in educating children according to the growth period.